Triangular umbilicoplasty with skin flap Umbilicoplastia triangular com retalho dérmico - João Francisco do Valle Pereira; Luciano Vargas Schutz; Velibor Kostic; Conrado Luiz Pais D'Avila; Felipe Nascimento Mateus (Revista Brasileira de Cirurgia Plástica, 2011)
BACKGROUND: Umbilicoplasty techniques vary greatly, in both the manner in which the incision the umbilical scar is incised, as well as the manner in which the skin of the abdominal flap is opened and repaired at the aponeurosis and/or the umbilical stump. As the postoperative appearance of the umbilical scar is aesthetically unsatisfying, the authors sought to develop a new technique aimed at providing patients with a greater degree of aesthetic and postoperative satisfaction. METHODS: The abdominoplasties included in this study were performed in 194 patients at Clínica Valle Pereira (Florianópolis, SC) between February 2009 and January 2011. All patients underwent conventional abdominoplasties and triangular umbilicoplasties with skin flaps. RESULTS: Only 8 (4.13%) patients had mild complications. There were no severe complications. Positive satisfaction was reported by patients in 188 (96.91%) cases and by surgeons in 186 (95.88%) cases. CONCLUSIONS: The technique described in this study demonstrates versatility, simplicity in application, and reproducibility, bringing greater harmony in body contouring and improved appearance of the umbilical scar, a major stigma of abdominoplasty INTRODUÇÃO: A técnica de umbilicoplastia varia muito, tanto na forma como é incisada a cicatriz umbilical, quanto na abertura cutânea no retalho abdominal e sua fixação na aponeurose e/ou coto umbilical. Descontentes com o aspecto pós-operatório da cicatriz umbilical, os autores viram a necessidade de desenvolver uma nova técnica, com o objetivo de proporcionar aos pacientes maior grau de naturalidade e satisfação pós-operatória. MÉTODO: Foram incluídas neste estudo as abdominoplastias realizadas na Clínica Valle Pereira (Florianópolis, SC), no período compreendido entre fevereiro de 2009 e janeiro de 2011, totalizando 194 pacientes. Todos os pacientes foram submetidos a abdominoplastia convencional e umbilicoplastia triangular com retalho dérmico. RESULTADOS: Apenas 8 (4,13%) pacientes apresentaram complicações leves. Não houve complicações graves. A satisfação dos pacientes foi positiva em 188 (96,91%) casos; entre os cirurgiões, a satisfação foi positiva em 186 (95,88%) casos. CONCLUSÕES: A técnica demonstra versatilidade, facilidade de execução e reprodutibilidade, proporcionando harmonia no contorno corporal e naturalidade ao principal estigma da abdominoplastia, a cicatriz umbilical